Collapse Prevention seismic performance assessment of new buckling-restrained braced frames using ASCE 41. (1st June 2018) - Speicher, Matthew S.; Harris, John L.
Highlights: Archetype BRBFs are designed with ASCE 7-10 and then assessed with ASCE 41-13. Archetype BRBFs are assessed using current performance-based design methods. Linear analysis results indicate minor performance issues in the columns and no performance issues in the braces. Nonlinear results indicated failures in the braces, suggesting the newly designed frame needs retrofitted. Effects of ground motion selection and alternative assessment criteria are discussed. Abstract: This paper presents the results of a seismic performance assessment using ASCE 41-13 for six buckling-restrained braced frames (BRBFs) designed in accordance with the 2012 International Building Code . The correlation between ASCE 7-10 and ASCE 41-13 is investigated to compare the seismic performance anticipated by the two standards. Three archetype buildings (4-, 8-, and 16-story) with BRBFs along one principal direction are designed for seismic effects: (1) once using the equivalent lateral force (ELF) procedure and (2) a second time using the response spectrum analysis (RSA) procedure. Performance assessments are conducted using four analysis procedures, static and dynamic analyses performed under both linear and nonlinear analysis regimes. Linear analysis results indicate minor performance deficiencies in the columns and the braces. Surprisingly, the nonlinear analysis results indicate more performance deficiencies in the braces, which is opposite of the general expectation that a more sophisticated analysis would yield a less conservative result. The contributing factors to the performance deficiencies are investigated. Recommendations are made on how to alter the performance outcome such as using alternative ground motion selection approaches (e.g., conditional mean spectrum) and having acceptance criteria based on cumulative ductility demands.